Using the prescribing cascade in equine practice. Issue 2 (5th March 2020) - Redpath, Adam; Bowen, Mark
Abstract : Background: The prescribing cascade is one of most discussed parts of the Veterinary Medicines Regulations 2013. It is referred to in guidance notes from the Veterinary Medicines Directorate (VMD) and forms part of the RCVS Code of Professional Conduct for Veterinary Surgeons. However, the dual role of horses as either food‐ or non‐food‐producing animals further complicates its application to everyday equine practice. Aim of the article: This review aims to illustrate ways in which the authors apply the prescribing cascade using clinical scenarios. It will also highlight differences between guidance from the RCVS and VMD, as well as aspects that may change as a result of changes in UK and EU regulations.